TINJAUAN HUKUM TERHADAP FUNGSI SERIKAT BURUH, PERUNDINGAN KOLEKTIF, DAN MOGOK KERJA DALAM HUBUNGAN INDUSTRIAL - Galuh Gilang Gumintang (PT. Saha Kreasi Indonesia, 2026)
Industrial relations is a system that regulates the relationship between workers, employers, and the government in order to achieve a balance of interests in the world of work. In that system, labor unions, collective bargaining, and strikes play a very important role as legal instruments in creating fair and harmonious labor relations. This research aims to examine the legal regulations regarding the functions of labor unions, the mechanisms of collective bargaining, and the right to strike from the perspective of labor law in Indonesia. The research method used is the normative juridical method with a legislative and conceptual approach. The research results show that labor unions have the primary function of representing workers in advocating, protecting, and defending workers' interests in industrial relations. Collective bargaining becomes the main mechanism in determining working conditions thru a negotiation process between labor unions and employers, resulting in a collective labor agreement as the legal basis for the employment relationship. Meanwhile, strikes are recognized as a worker's right used as a last resort if negotiations do not reach an agreement, provided they are carried out in accordance with applicable legal procedures. The conclusion of this research shows that these three aspects are interconnected and are an important part of creating a balanced and fair industrial relationship. However, in its implementation, there are still various challenges such as the imbalance of bargaining power between workers and employers, as well as the effectiveness of labor law enforcement.